KONFIGURASI SETTING RELAY TEGANGAN NOL (RTN) PADA GARDU INDUK (GI) MASAMBA - Muhtar, Muhdalifah; Amri, Nurul Amalia; Nurfadhilah, Annisa; Ridhwan, Muhammad (TECHNO-SOCIO EKONOMIKA, 2024)
Masamba Substation (GI), located at the endpoint of the Sulselrabar electrical system, often experiences disruptions due to high lightning activity. These disruptions can lead to transformer energization under load conditions, posing risks of significant transformer damage and destabilizing the electrical system. To address this, an effective protection scheme is needed. The Zero Voltage Relay (RTN) is designed to prevent transformer energization under load, making it crucial to configure and test RTN at Masamba GI. This study aims to implement the RTN protection scheme and determine the optimal configuration to protect the transformer and maintain electrical system stability at Masamba GI. Given the frequent disruptions and associated risks, a quantitative method was employed. This included collecting technical data from GI equipment, testing the RTN configuration using the MiCOM P143 relay, and analyzing undervoltage and undercurrent parameters as RTN trigger inputs. The results demonstrated that the RTN operated effectively, automatically releasing the load during disturbances, thereby preventing transformer energization under load. The applied RTN settings increased the selectivity and reliability of the protection system, ensuring the RTN only activated during critical situations. This not only prevented potential transformer damage but also contributed to extending its lifespan and improving overall system stability. The RTN configuration at Masamba Substation proves to be a reliable solution for mitigating risks associated with frequent lightning-induced disruptions, enhancing both protection and system resilience.